1996
DOI: 10.1016/0735-1097(95)00583-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ischemic response during exercise and dobutamine echocardiography in patients with left main coronary artery disease

Abstract: On the basis of changes in regional wall motion both dobutamine and exercise echocardiography have a comparable high sensitivity in diagnosing myocardial ischemia in left main coronary artery disease. However, conventional signs of severe myocardial ischemia, including left ventricular cavity dilation and marked ST segment depression, occur more often with exercise than with dobutamine echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…In addition, our data provide invasive quantitative support for the concept that the increase in MVO2 at peak DSE is modest despite marked chronotropic and inotropic effects. [6][7][8] This limitation in increase in MVO2 at peak DSE is likely a consequence of a net decrease in ESWS. 2 The reduction in wall stress during DSE is driven by a reduction in LV volumes, reflected hemodynamically by a decrease in PCWP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our data provide invasive quantitative support for the concept that the increase in MVO2 at peak DSE is modest despite marked chronotropic and inotropic effects. [6][7][8] This limitation in increase in MVO2 at peak DSE is likely a consequence of a net decrease in ESWS. 2 The reduction in wall stress during DSE is driven by a reduction in LV volumes, reflected hemodynamically by a decrease in PCWP.…”
Section: Discussionmentioning
confidence: 99%
“…5 The effectiveness of dobutamine for increasing MVO 2 compared with exercise has been questioned. [6][7][8] Lower end-systolic wall stress has been implicated as a primary cause for reducing the sensitivity of DSE for detection of CAD. 9 One safe adjunct that has been used to increase the sensitivity of DSE for the detection of functionally significant CAD is the addition of isometric exercise in the form of sustained submaximal handgrip (HG) at peak DSE.…”
Section: Introductionmentioning
confidence: 99%
“…However, the hemodynamic response to the stress of dobutamine differs from that of exercise. 10 Investigation of Doppler-derived diastolic filling pressure with DSE may provide important insights, but further investigation is needed.…”
mentioning
confidence: 99%
“…Previous studies have found that an abnormal LVESV response during stress echocardiography is associated with severe CAD [31][32][33] and worse prognosis. 12 It is likely that patients with more extensive ischemia induced by dobutamine exhibit an abnormal LVESV response, and thus it is a more important prognostic finding than the binary DSE criteria (positivity on DSE).…”
Section: Discussionmentioning
confidence: 99%